Pengaruh Current Ratio, Return on Equity, dan Total Asset Turnover Terhadap Underpricing Pada Penawaran Umum Perdana (Studi Empiris Pada Perusahaan Go Public di Bursa Efek Indonesia) - Debi Carolina (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2020)
The development of the company make the needs will be adding more capital. The Capital Market to alternative sources of funds in addition to banks for financing the financing of the activities of the operation of the company through the sale of the shares and the issuance of bonds by companies that require funds. The presence of the capital market is currently very important for the company and investors. The formulation of the problem in this research is : 1. How the influence of the Current Ratio, Return On Equity and Total asset turnover against Underpricing on public offering on the go public company securities bourse indonesia year 2015-2017 simultaneously?,2. How the influence of the Current Ratio, Return On Equity and Total asset turnover against Underpricing on public offering on the go public company securities bourse indonesia year 2015-2017 partially?. This research aims to find out the influence of the Current Ratio, Return On Equity and Total asset turnover against Underpricing on Public Offering on the go public company in Indonesia Stock Exchange Year 2015-2017 good partially or simultanously. The object of this research is a company go public company to conduct a Public Offering in Indonesia Stock Exchange the year 2015-2017. The sampling is done using purposive sampling with the number of samples is used as much as 33 (thirty-three companies that are experiencing underpricing on public offering in Indonesia Stock Exchange period 2015-2017. The secondary data source in this research took from BEI. The methods in use in this research is a quantitative and qualitative research method. Data analysis techniques using multiple regression analysis double linier. Based on the results of the analysis produced by the Current Ratio, Return on Equity and Total Asset Turnover positive effect underpricing simultaneously, while Total Asset Turnover positive effect on underpricing partially Current Ratio and Return on Equity does not affect Underpricing partially.